O modelo processual cooperativo intersubjetivo aplicado às ocupações irregulares consolidadas em áreas urbanas de preservação permanente - Barbosa, Alessander Santos (2018)
This research tackles the problem of irregular occupations taken up and consolidated in urban areas of permanent environment preservation, as historical reflection of the disorderly urban growth and of the failure of constitutional public housing and sustainable city policies. The factual context of occupations fuels complex collective judicial litigation, in which it is intended to accommodate the tension, evidently existing, between the fundamental rights to decent housing and the ecologically balanced environment, also doubly violated. Thus, based on the observation that we are experiencing a structural socio-environmental problem, which has not encountered an effective response in the hermetic application of the legislation, we intend to use the method of revising the literature, documental research, and the inductive method of case analysis to identify the most appropriate procedural position to the parties at this conjuncture. With theoretical foundation in the neo-proceduralism, fresh fruit of neo-constitutionalism, and in the theory of fraternity as a constitutional juridical category, we defend the hypothesis that the present procedure model demands some conduction based on ample and unrestricted cooperation among all procedural subjects, and that, in the ambience of collective processes of the species, where litigants have a clear common primary public interest, will be the most efficient way to obtain a fair judicial decision, in a reasonable and effective period of time.